Informing our understanding of the copper–cuprizone reaction with computational chemistry. Issue 27 (29th June 2022) - Pushie, M. Jake; George, Graham N.
Abstract : The coordination chemistry of copper–cuprizone has presented considerable challenges for over 70 years. Using computational chemistry we elucidate key events in copper–cuprizone complex formation, including the asymmetric hydrolysis of cuprizone. Abstract : The reaction of copper with bis(cyclohexanone)oxaldihydrazone (cuprizone) is a challenging coordination chemistry problem that has confounded attempts at elucidation for the past 70 years. The product of the reaction, a blue copper complex, wherein the cuprizone ligand is hydrolyzed, has been the primary focus during its history. We have recently characterized an additional green multi-copper product which contains unhydrolyzed cuprizone, which only added to the mystery. Using density functional structure models and thermodynamic calculations we address several of the long-standing questions surrounding the copper–cuprizone reaction, as well as identify the likely reaction pathway that gives rise to the blue and green products. Cu(ii )-induced asymmetric hydrolysis of the cuprizone ligand is essential for formation of the blue product, followed by a series of Cu(ii )-induced deprotonation and coordination events, with complex formation terminating with hydrolyzed cuprizone tautomerization and intramolecular electron transfer, generating a pseudo-macrocyclic Cu(iii ) species. Alternatively, in the presence of excess Cu(ii ), or in non-aqueous solvents, a green multi-Cu(ii ) complex forms comprised of alternating Cu(ii )–cuprizone units. Structure calculations are supported by experimental data and represent the most rigorous approach to-date toward understanding the complex solution chemistry of copper with cuprizone.